Herbicidal potential of lavender (Lavandula angustifolia Mill.) essential oil components on bristly foxtail (Setaria verticillata (L.) P. Beauv.): comparison with carvacrol, carvone, thymol and eugenol - Koiou, Katerina; Vasilakoglou, Ioannis; Dhima, Kico (Archives of Biological Sciences, 2020)
Paper description: The phytotoxicity of ten major essential oil components of lavender on the weed bristly foxtail was determined in a perlite-based Petri dish bioassay. Terpinen-4-ol, lavandulol and linalyl acetate exhibited similar phytotoxicity to carvone, thymol and carvacrol. A synergistic effect was observed when carvacrol or eugenol were combined with ocimene, 3-octanone, α-terpineole or terpinen-4-ol. Lavender essential oil components could be regarded as active ingredients for the production of natural herbicides. Abstract: Essential oils are a plentiful source of plant compounds for potential use in the development of natural herbicides. With this in mind, the phytotoxicity of ten major essential oil components of lavender (Lavandula angustifolia Mill.) on the weed species bristly foxtail (Setaria verticillata (L.) P. Beauv.) was determined using a perlite-based Petri-dish bioassay. Their phytotoxicity was also compared with that of well-known phytotoxic essential oil components (carvacrol, thymol, carvone and eugenol) of oregano (Origanum vulgare L.) and clove (Syzygium aromaticum (L.) Merr. & L.M. Perry) essential oils. Potential synergistic or antagonistic effects between carvacrol or eugenol with other components of lavender essential oil were investigated. Regarding the most phytotoxic components, terpinen-4-ol at 80 nL/cm3 completely inhibited the germination and root length of bristly foxtail, displaying similar phytotoxicity to carvone and thymol. Like carvacrol, lavandulol and linalyl acetate caused total (100%) germination and root length reduction of bristly foxtail at 160 nL/cm3, while the same effect was achieved by lavandulyl acetate at 320 nL/cm3. A synergistic effect was also observed when carvacrol or eugenol were combined with ocimene, 3-octanone, α-terpineol or terpinen-4-ol. Focusing on the development of alternative weed control strategies, lavender essential oils containing high concentrations of terpinen-4-ol, lavandulol or linalyl acetate could be useful for the production of natural herbicides. These essential oil components combined with selected oregano or clove essential oil components, increase phytotoxicity and weed control due to the synergistic effect observed when in mixture. https://doi.org/10.2298/ABS200106016K Received: January 6, 2020; Revised: April 10, 2020; Accepted: April 11, 2020; Published online: April 22, 2020 How to cite this article: Koiou K, Vasilakoglou I, Dhima K. Herbicidal potential of lavender (Lavandula angustifolia Mill.) essential oil components on bristly foxtail (Setaria verticillata (L.) P. Beauv.): comparison with carvacrol, carvone, thymol and eugenol. Arch Biol Sci. 2020;72(2):223-31.